Single mammalian cell encapsulation by in situ polymerization. Issue 47 (16th November 2016) - Yang, Jianmin; Li, Jingchao; Wang, Xinlong; Li, Xiaomeng; Kawazoe, Naoki; Chen, Guoping
Abstract : Encapsulation of single mammalian cells with a cytoprotective polymeric shell through two mild reaction steps, surface acryloylation and in situ polymerization. Abstract : Encapsulation of single mammalian cells with biocompatible and protective materials has important applications in biomedical and single-cell biology research. To date, single mammalian cells have generally been encapsulated by physical approaches including hydrophobic and electrostatic interactions. However, the cytotoxicity of the used materials, short sustained period, and especially loose structure of the encapsulation layer have limited the application of the encapsulated cells. Here, we show a novel strategy based on in situ polymerization for encapsulation of single mammalian cells with a network structure of the polymeric shell under mild conditions. Using the present strategy, the encapsulated mammalian cells, HeLa cells, hMSCs, and BACs showed high viability. Furthermore, the encapsulation shell was able to prevent the penetration of macro-external entities, while maintaining the free exchange of smaller molecules. This work provides a new and versatile method for single mammalian cell encapsulation.